2005
DOI: 10.1002/agr.20043
|View full text |Cite
|
Sign up to set email alerts
|

Consumer, retailer, and producer assessments of product differentiation according to regional origin and process quality

Abstract: Regional marketing concepts can be a successful strategy for product differentiation. A research project in Northern Germany reveals the following results: consumers' stated preferences show clearly potential demand for regional food, in particular if environment-friendly produced and controlled. The main influencing factors that could be identified by means of a rank-ordered logit analysis are consumers' regional, nutrition, and environment consciousness as well as a low price sensitivity and mistrust in conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…They concluded that producers may be able to reach different segments by providing consumers with different types of information and that demographic characteristics alone do not accurately predict natural beef consumers. Results from other research suggest that consumer attitudinal and preference variables such as knowledge, motivation, risk preferences, environmental and social consciousness play a large role in determining consumer preferences for credence attributes (Baker & Burnham, 2000;Huffman, Shogren, Rousu, & Tegene, 2003;Umberger et al, 2003;Wirthgen, 2005).…”
Section: Previous Researchmentioning
confidence: 96%
See 2 more Smart Citations
“…They concluded that producers may be able to reach different segments by providing consumers with different types of information and that demographic characteristics alone do not accurately predict natural beef consumers. Results from other research suggest that consumer attitudinal and preference variables such as knowledge, motivation, risk preferences, environmental and social consciousness play a large role in determining consumer preferences for credence attributes (Baker & Burnham, 2000;Huffman, Shogren, Rousu, & Tegene, 2003;Umberger et al, 2003;Wirthgen, 2005).…”
Section: Previous Researchmentioning
confidence: 96%
“…Previous researchers examining consumers' perceptions of meat quality have found that consumers use a combination of search, experience, and credence attributes to determine the quality of meat products (Umberger, 2004(Umberger, , 2007Wirthgen, 2005). Past studies have used neoclassical demand theory as the basis for determining consumer segments willing to pay more for meat products labeled with credence attributes such as ''natural,'' ''organic,'' ''free-range,'' ''GMO-free,'' ''produced without the use of hormones and/or antibiotics,'' ''certified humane,'' ''environmentally friendly,'' and ''local'' to name a few (Baker & Burnham, 2001;Dickinson & Bailey, 2002;Loureiro & Umberger, 2003, 2005Lusk & Fox, 2002;Lusk, Roosen, & Fox, 2003;McGarry-Wolf & Thulin, 2000;Thilmany, Grannis, & Sparling, 2003;Umberger, Feuz, Calkins, & Sitz, 2003;Wirthgen, 2005).…”
Section: Previous Researchmentioning
confidence: 97%
See 1 more Smart Citation
“…Codron et al show that recently, ethical, health and environmental values become increasingly more important for consumers (2006). Wirthgen (2005) also indicates that marketing on "the regional origin" can be a successful strategy for product differentiation. Thus as consumers perceive that organic products score very well on these points, some retailers may develop organic, fair trade and sustainable products strongly to enforce their image as social responsible retailer.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…), but much less by considering various stakeholders (Wirthgen 2005) or from a strategic management point of view. An exception is presented by Hanf and Kühl (2005) for the branding strategy of the retail.…”
mentioning
confidence: 99%